Supported metal and metal oxide particles with proximity effect for catalysis. Issue 58 (25th September 2020) - Biswas, Subhadeep; Pal, Anjali; Pal, Tarasankar
Abstract : Catalysts are empowered with proper support materials (SM). The proximity effect, in other word 'synergism' between the two, is still necessary to be explored at the molecular level to revamp this never ending field of catalysis. Abstract : External influence is essential for any change to occur in this world. Similarly, the reaction path of a chemical reaction can be changed with the addition of a catalyst from outside. Sometimes a catalyst performs better when it remains associated with an inert substance, which is called a support material (SM). Improved catalyst accomplishment arises from the 'proximity effect'. Even inert supports play a role in better product formulation or environmental remediation. In this review, it has been shown how the SM, as a nest, aids the catalyst particle synergistically to perform a good job in a chemical reaction. The structure–function relationship of SM helps in catalyst activation to some extent, and produces active centres that are difficult to fully ascertain. In the text, Langmuir–Hinshelwood (L–H), Mars-van Krevelen (MVK), and Eley–Rideal (E–R) mechanisms are highlighted for the adsorption processes as the case may be. Again, the importance of SM for both catalyst and substrates has been consolidated here in the text. Finally, the role of the initiator and the promoter is also discussed in this review.